H,K-ATPase and carbonic anhydrase response to chronic systemic rat gastric hypoxia (Medical Journal of Indonesia, 2015)
Background: Hypoxia may induce gastric ulcer associated with excessive hidrogen chloride (HCl) secretion. Synthesis of HCl involves 2 enzymes, H,K-ATPase and carbonic anhydrase (CA). This study aimed to clarify the underlying cause of gastric ulcer in chronic hypoxic condition, by investigating the H,K-ATPase and CA9 response in rats.Methods: This study was an in vivo experiment, to know the relationship between hypoxia to expression of H,K-ATPase and CA9 mRNA, and H,K-ATPase and total CA specific activity of chronic systemic rat gastric hypoxia. The result was compared to control. Data was analyzed by SPSS. If the data distribution was normal and homogeneous, ANOVA and LSD post-hoc test were used. However, if the distribution was not normal and not homogeneous, and still as such after transformation, data was treated in non-parametric using Kruskal-Wallis and Mann Whitney test. Twenty five male Sprague-Dawley rats were divided into 5 groups: rats undergoing hypoxia for 1, 3, 5, and 7 days placed in hypoxia chamber (10% O2, 90% N2), and one control group. Following this treatment, stomach of the rats was extracted and homogenized. Expression of H,K-ATPase and CA9 mRNA was measured using real time RT-PCR. Specific activity of H,K-ATPase was measured using phosphate standard solution, and specific activity of total CA was measured using p-nitrophenol solution.Results: The expression of H,K-ATPase mRNA was higher in the first day (2.159), and drastically lowered from the third to seventh day (0.289; 0.108; 0.062). Specific activities of H,K-ATPase was slightly higher in the first day (0.765), then was lowered in the third (0.685) and fifth day (0.655), and was higher in the seventh day (0.884). The expression of CA9 mRNA was lowered progressively from the first to seventh day (0.84; 0.766; 0.736; 0.343). Specific activities of total CA was low in the first day (0.083), and was higher from the third to seventh day (0.111; 0.136; 0.144).Conclusion: In hypoxia condition, expression of H,K-ATPase and CA9 mRNA were decreased, but the specific activity of H,K-ATPase and total CA were increased.